2019
DOI: 10.1111/jfpp.14146
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical properties, antioxidant capacity, and total phenolic content of xyloglucan component in tamarind ( Tamarindus indica ) seed extracted using subcritical water

Abstract: Tamarind kernel powder was utilized as raw material for xyloglucan component extraction. The main aims were to determine the potential of applying subcritical water in xyloglucan component extraction and to investigate effects on yield and properties of extracted xyloglucan components. Ratio of tamarind kernel powder to water for all extractions was 1:20 (w/v) with extraction temperatures of 100–200°C. Extracted xyloglucan component samples were determined for their color, pasting property, viscosity, water ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The extraction pressure range is 250–500 MPa for 5–15 min. The HPP‐treated mixture is subjected to the same protease enzyme and alcohol precipitation process (Limsangouan et al ., 2019).…”
Section: Methods Used For the Production Of Xyloglucanmentioning
confidence: 99%
See 2 more Smart Citations
“…The extraction pressure range is 250–500 MPa for 5–15 min. The HPP‐treated mixture is subjected to the same protease enzyme and alcohol precipitation process (Limsangouan et al ., 2019).…”
Section: Methods Used For the Production Of Xyloglucanmentioning
confidence: 99%
“…Therefore, enzyme hydrolysis is used in HWE, increasing the yield and purity of obtained XG. Limsangouan et al (2019) reported that XG is extracted from defatted TKP by dissolving in distilled water, boiling, followed by enzyme hydrolysis with protease and then centrifuged, filtered, precipitated with ethanol and dried.…”
Section: Hot and Cold Water Or Conventional Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a novel process, such as subcritical water extraction, is required to upgrade the xyloglucan production process (Limsangouan et al, 2019). Limsangouan et al (2019) used a subcritical water extraction method in xyloglucan production. They reported maximum yield as 62.28% at an extraction temperature of 175°C, which was higher as compared with the methods followed by other researchers.…”
Section: Tamarind Seed Productsmentioning
confidence: 99%
“…and converted into powder.The utilization of boiling for the extraction of xyloglucan has some limitations such as longer extraction time, use of a large amount of solvents, lower extraction yield, and alteration in the properties(Kulkarni et al, 2017). Therefore, a novel process, such as subcritical water extraction, is required to upgrade the xyloglucan production process(Limsangouan et al, 2019). Limsangouan et al (2019) used a subcritical water extraction method in xyloglucan production.…”
mentioning
confidence: 99%